1995
DOI: 10.5271/sjweh.61
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk among workers in biomedical research

Abstract: Objective This epidemiologic study was undertaken after a cluster of five cases of rare forms of cancer (bone sarcoma, non-Hodgkin's lymphoma) had been observed among biomedical research workers at the Pasteur Institute in Paris to ascertain whether their disease was connected with exposure during this research. Methods A mortality study included 3765 people who worked at the Pasteur Institute between 1971 and 1986 and were followed until the end of 1987. Within this cohort a nested case-referent study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 16 publications
6
22
1
Order By: Relevance
“…There is also a non-significant elevation of brain cancer deaths among females, a finding that is consistent with other studies of laboratory workers [Olin and Ahlbom, 1980;Belli et al, 1992;Hunter et al, 1993;Cordier et al, 1995]. The women who died of brain cancer were employed primarily in production assay laboratories at the K-25 facility during the very early years of plant operations when exposures to solvents, metals, and acids were likely.…”
Section: Discussionsupporting
confidence: 79%
“…There is also a non-significant elevation of brain cancer deaths among females, a finding that is consistent with other studies of laboratory workers [Olin and Ahlbom, 1980;Belli et al, 1992;Hunter et al, 1993;Cordier et al, 1995]. The women who died of brain cancer were employed primarily in production assay laboratories at the K-25 facility during the very early years of plant operations when exposures to solvents, metals, and acids were likely.…”
Section: Discussionsupporting
confidence: 79%
“…Consequently, it was only in the last 10 years that results became available (Table IX) [Cordier, 1990;Belli et al, 1992;Daly et al, 1994;Cordier et al, 1995;Brown et al, 1996;Wennborg et al, 1999;Vecchio et al, 2001;Wennborg et al, 2001]. Despite a lower overall cancer mortality than among the general population, these research workers showed an excess risk of cancer of certain sites: brain, pancreas, lympho-hematopoietic system, and bone.…”
Section: Other Exposuresmentioning
confidence: 99%
“…In particular, Cordier's case-control study of Pasteur workers found an association with work in molecular biology and microbiological genetics, and with the use of agents, such as ethidium bromide, acrylamide, methyl-nitronitrosoguanidine, ethyl methanesulfonate, acridine orange, bacteria, and recombinant DNA, and radioactive compounds such as 32 P. Those employed in microbiology and medical bacteriology appeared to be at highest risk for bone and pancreatic cancer, and brain tumors. Microbial genetics and molecular biology was associated with lymphatic and hemopoietic cancer, however, the number of subjects was small [Cordier et al, 1995]. Case reports have also implicated nitrosoguanidine [Pleven et al, 1984].…”
Section: Other Exposuresmentioning
confidence: 99%
“…In 1995, Cordier et al found an increased relative risk of PC among female biomedical research workers at the Pasteur Institute in Paris, France (SMR ¼ 490;95%CI: 158-1144) [Cordier et al, 1995]. Increased risk was also noted mainly for bone cancer, and the authors hypothesized a possible causal relation for exposure to genotoxicants like ethidium bromide, acrylamide, methylnitronitrosoguanidine, ethylmethanesulfonate, and radioactive compounds.…”
Section: Introductionmentioning
confidence: 99%